2023
DOI: 10.1186/s40795-023-00737-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet and bowel function in children with Hirschsprung’s disease: development and content validation of a patient-reported questionnaire

Abstract: Background Although dietary adjustments are recommended frequently for bowel symptoms, evidence of diet’s impact on bowel function is lacking. The aim was to develop a patient-reported outcome instrument, for children with and without Hirschsprung’s disease (HD), to explore experiences of dietary effects on bowel function. Methods Children with and without HD and their parents participated. Questionnaire items regarding the impact of diet on bowel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Out of 345 articles identified by the database searches, 49 articles met the inclusion criteria. 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Most concerned esophageal atresia ( n = 17) and Hirschsprung's disease ( n = 14). None of the articles focused on duodenal atresia or omphalocele.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 345 articles identified by the database searches, 49 articles met the inclusion criteria. 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Most concerned esophageal atresia ( n = 17) and Hirschsprung's disease ( n = 14). None of the articles focused on duodenal atresia or omphalocele.…”
Section: Resultsmentioning
confidence: 99%
“…The 49 articles identified a total of 29 PROMs. 66 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 The most frequently used PROM, applied predominantly in patients with esophageal atresia ( n = 11) or Hirschsprung's disease ( n = 8), was the Pediatric Quality-of-Life Inventory 4.0 generic core scales (PedsQL 4.0) 83 ( n = 31). Four common assessments for colorectal function, including (in)continence, in anorectal malformations and/or Hirschsprung's disease were the Rintala Bowel Function Scoring System 77 ( n = 9), Baylor Continence Scale (BCS) 78 ( n = 4), Cleveland Clinic Fecal Incontinence Severity Scoring System (or Wexner score) 81 82 ( n = 2), and the Krickenbeck criteria 102 ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal symptoms were assessed by questions about constipation (Rintala Bowel (18). This instrument was developed for children aged 1-18 years old and their parents.…”
Section: Study Questionnairementioning
confidence: 99%
“…In our focus group study, diet was shown to play a key role in parental self-treatment of GI symptoms in children with HD, and such changes have an impact on daily life [ 12 ]. To increase knowledge on diet’s role in bowel function, we developed the Diet and Bowel Function Questionnaire [ 13 ]. In healthy children who answered the questionnaire, any GI effects as a result of diet were only evident among 52%, and the reported effects were weak [ 14 ].…”
Section: Introductionmentioning
confidence: 99%